The Issue of the Main Character in the Novel "Kecha Va Kunduz" - Boltaboyev Omonboy (Genius Journals, 2022)
This article analyzes the system of characters and main character in Cholpon's novel "Kecha Kunduz", as well as the writer's skill in character drawing.
Keywords: image; character; protagonist; psyche